177k views
0 votes
Express log base a of x + 1/2log base a of y as a single logarithm.

User Mpb
by
5.8k points

2 Answers

5 votes

Answer:

see explanation

Explanation:

Using the rules of logarithms

log
x^(n) ⇔ n log x

log x + log y ⇔ log xy

Given


log_(a) x +
(1)/(2)
log_(a) y

=
log_(a) x +
log_(a)
y^{(1)/(2) }

=
log_(a) (x
y^{(1)/(2) } )

=
log_(a) ( x
√(y) )

User Dezzan
by
7.3k points
4 votes

Answer:
\bold{log_a(xy^{(1)/(2)})}

Explanation:


log_a(x)+(1)/(2)log_a(y)\\\\\text{Use the rules for condensing}\\\bullet \text{coefficient becomes exponent}\\\bullet \text{addition becomes multiplication}\\\\.\quad log_a(x)+log_a(y)^{(1)/(2)}\\= log_a[(x)(y)^(1)/(2)]\\= log_a(xy^{(1)/(2)})\\\\\\\text{This can also be written as: }log_a(x√(y))

User Marne
by
6.2k points